Synthesis of hybrid materials functionalized with cyano-ionic liquid for the extraction of chlorophenols and polycyclic aromatic hydrocarbons / Shabnam Bakhshaei - Shabnam , Bakhshaei (2016)
In the present study two new cyano/ionic liquid functionalized hybrid materials were successfully synthesised based on immobilization of cyanopropyltriethoxysilane and 1-benzyl-3-(trimethoxysilylpropyl)imidazolium chloride ionic liquid (BTMP-IM) on the surface of titanium (IV) butoxide and Fe3O4 magnetic nanoparticle to enhance extraction capability toward aromatic moieties.The cyano/ionic liquid functionalized silica-titania mixed oxide (Si-Ti@CN/IL) was prepared via sol-gel method in acidic condition and used as an adsorbent for preconcentration/separation of chlorophenols in aqueous samples prior to High-performance liquid chromatography (HPLC). The Si-Ti@CN/IL was characterised by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET), elemental analysis with CHNS and X-ray diffraction (XRD) to support the structure of this new hybrid material. The new Si-Ti@CN/IL adsorbent shows a good performance for extraction of selected chlorophenols (CPs) in aqueous samples with high recovery and low limit of detection (LOD = 0.83 – 0.95 g L-1) with linearity range from 10 – 100 g L-1, meanwhile, limit of quantification (LOQ) was between 2.77 to 3.17 g L-1. The application of Si-Ti@CN/IL for environmental samples was successfully studied on tap water, lake water and leachate from landfill site. The results obtained high recovery (73.39 – 105.54 %) with good precision (%RSD: 0.82 – 4.19). The cyano/ionic liquid functionalized Fe3O4 magnetic nanoparticle (MNP@CN/IL) was synthesised via basic co-precipitation and sol-gel methods and used as an adsorbent for preconcentration/separation of polycyclic aromatic hydrocarbons (PAHs) and chlorophenols (CPs) in aqueous and soil samples through magnetic solid phase extraction (MSPE) prior to HPLC. The MNP@CN/IL was characterized by FT-IR, XRD, transmission electron microscopy (TEM), elemental analysis with EDX as well as CHNS and TGA. The magnetic properties of the adsorbent was analysed by vibrating sample magnetometer (VSM). The MNP@CN/IL shows good performance with high recovery and low LOD (0.42 – 0.76 g L-1 for PAHs) and (0.64 – 1.06 g L-1 for CPs) with linearity range from 0.1 – 100 g L-1for PAHs and 3 – 100 g L-1 for CPs. Meanwhile the LOQ for PAHs and CPs were 1.39 – 2.55 g L-1 and 2.15 – 3.54 g L-1. The application of MNP@CN/IL for environmental samples was successfully studied on leachate and sludge from landfill site. The results obtained high recovery (83.75 – 115.33 % for PAHs) and (77.67 – 112.8 % for CPs) with acceptable precision (%RSD: 1.00 – 4.49 for PAHs; 0.92 – 4.89 for CPs).